Media, Ranah dan Dinamika Permainan - Amirudin Amirudin (Endogami: Jurnal Ilmiah Kajian Antropologi, 2017)
In the 21st century, the media is increasing rapidly and requires a specific response from anthropology studies. Not only does the media bring with implications for changes in the process of production and consumption of culture, but also changes to its viewpoint and approach. It's not enough if the media was studied only with a classical perspective that only positioned the media as a cultural communication agent, or otherwise the media is approached with the effects study. However, the media also needs to be recognized with a more progressive perspective that positions the media as an agency in cultural production practices. Based on the idea, this paper provides provocation through Amirudin's research (2016) which tried to present a new perspective in media studies